2019
DOI: 10.1007/s11249-019-1158-7
|View full text |Cite
|
Sign up to set email alerts
|

How Sliding and Hydrodynamics Contribute to Articular Cartilage Fluid and Lubrication Recovery

Abstract: The tribological functions of cartilage are governed primarily by its interstitial fluid content, but the means by which cartilage recovers and retains interstitial fluid during articulation following periods of static loading remain unclear. Recently, we demonstrated a phenomenon in which articular cartilage recovers fluid at the loaded contact interface; we refer to this as 'tribological rehydration'. Our findings were consistent with two competing hypotheses: (1) that hydrodynamic pressures exceeded local i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Otherwise, the wedge effect on the friction behavior of PVA/GO hydrogel is considered for different counterface ball diameter. It has been reported that the friction coefficient of cartilage was mainly related to rehydration induced by the wedge effect and the compressing of liquid into the porous surface during sliding [22,48]. The larger diameter of counter ball results in lower angle of wedge (Fig.…”
Section: Sliding Speed Load Counterface Diameter-dependent Frictionmentioning
confidence: 97%
See 1 more Smart Citation
“…Otherwise, the wedge effect on the friction behavior of PVA/GO hydrogel is considered for different counterface ball diameter. It has been reported that the friction coefficient of cartilage was mainly related to rehydration induced by the wedge effect and the compressing of liquid into the porous surface during sliding [22,48]. The larger diameter of counter ball results in lower angle of wedge (Fig.…”
Section: Sliding Speed Load Counterface Diameter-dependent Frictionmentioning
confidence: 97%
“…Therefore, the factor of ( a/h) was introduced to modify the values of maximum contact pressure, P H , and contact depth, H , calculated from the Hertzian contact equations. For the model of elastic layer with a thickness of h on a rigid body, the modification to the load ( F ′ ) and contact depth ( ′ ) with respect to their Hertzian counterparts can be obtained as follows, where is equal to 0.15 for low friction (close to a frictionless boundary condition) at the indenter interface [48]. The correction reported in Eq.…”
Section: Sliding Speed Load Counterface Diameter-dependent Frictionmentioning
confidence: 99%
“…Cartilage wear is because of PGs loss and alterations in the collagen network [ 63 ]. Cartilage wear could be initiated due to biochemical degradation and biomechanical factors such as knee misalignment, which induces higher pressure on either the medial or lateral side of the knee joint [ 64 ]. Most of the studies have fallen short of quantifying wear mechanism due to its complex nature; hence only frictional properties have been investigated.…”
Section: Tribological Properties Of Articular Cartilagementioning
confidence: 99%
“…Cartilage is a highly hydrated, avascular tissue that displays remarkably complex biomechanical behavior characterized by high compressive stiffness, strength, and lubricity. , Such complexity can be attributed to its layered nature (Figure ), wherein horizontally aligned collagen at the surface progresses to vertically aligned deeper in the tissue, resulting in the tissue’s anisotropic feature. Furthermore, it has a remarkable ability to expel and regain its water content (up to 80% by weight) during loading and articulation. , Toward materials-driven regeneration of cartilage, synthetic materials should recapitulate an environment that drives chondrogenesis through chondroconductivity, chondroinductivity, and chondrointegration. Chondroconductive scaffolds provide a morphology similar to that of the confined chondrocytic environment (smaller interconnected pores (<300 μm) with low porosity) to facilitate cell–cell interactions for chondrogenesis.…”
Section: Considerations For Osteochondral-instructive Scaffoldsmentioning
confidence: 99%